A STUDY OF VALIDITY AND RELIABILITY FOR THE SCALE OF SPIRITUAL INTELLIGENCE CHARACTERISTICS - Abdulkerim KARADENİZ; Davut AYDIN (International Journal of Eurasia Social Sciences, 2016)
It is obvious that not enough studies have been conducted on students’ spiritual intelligence characteristics in the relevant literature and there is no valid and reliable measurement tool, especially at the national level, regarding the identification of spiritual intelligence characteristics. In this context, the aim of this study is to develop a scale that can be used in measuring the spiritual intelligence characteristics of university students. Validity and reliability studies of the scale were carried out with the participation of a total of 1277 students. It was determined as a result of exploratory and confirmatory factor analysis that the scale had a 5 factor-structure which explained %52,21 of total variance. It was found that the Kaiser-Meyer-Olkin (KMO) coefficient of the scale was 0,927 and Barlett Test significance value was 0.000. Cronbah’s Alpha reliability coefficient of the scale was found to be 0,910. In addition, the consistency feature of the scale was examined to obtain information concerning the reliability of the scale and a test-retest method was used. The correlation between the two applications which can be shown as a proof for the consistency of the scale is ,85. Confirmatory factor analysis showed that the two-factor model fitted the data (x2= 147.60, sd= 95,p=0.00, RMSEA= .042, NFI= .98, CFI= .99, IFI= .99, RFI= .97, CFI= .99, GFI= .94, AGFI= .92, SRMR= .035).